Digital Learning Literacy and Business Education from an Islamic Perspective at High School in Malaysia - Iqbal Alan Abdullah; Putri Allana Abdullah; Abaidullah Bin Mustaffa; Dedi Satriawan; Basrowi Basrowi; Pertiwi Utami; Nur Azizah Zuhriyah (Universitas Nurul Jadid, 2024)
Partners in this program are teachers from the National High School or Bukit Katil State School (SMK) in Ayer Keroh, Melaka, Malaysia. The problem faced by partners is that there is still not optimal knowledge about the use of digital learning and business education from an Islamic studies perspective. Apart from that, several teachers have never attended seminars on developing business education which is very important for increasing their insight as teachers at the vocational school level. The teachers have never held discussion activities related to this topic face to face with lecturers or delegates from international universities. In relation to these problems, the problems are efforts to increase literacy, knowledge and insight of teachers regarding the use of digital learning and development of buying and selling businesses from an Islamic perspective through seminars and joint discussions, and efforts to increase Islamic economic and financial literacy, communication skills within the scope of business education development, for teachers together with lecturers from various universities in Indonesia. This activity purposes to identify partners' knowledge and insight in utilizing digital learning and business education effectively from an Islamic perspective. This activity is very useful for expanding and strengthening relationships between teachers and lecturers in related fields. This activity was carried out using the Forum Group Discussion method. After carrying out this international community service activity, the knowledge, literacy and understanding abilities of the teachers increased. This is demonstrated by their ability to answer various questions in the discussions held. The teachers are also quite enthusiastic in establishing good relationships with lecturers from various disciplines